Study on adhesion strength of tin coated biomedical ti-13zr-13nb alloy - Arman Shah, Abdullah; Izman, Sudin; Siti Nurul Fasehah, Ismail; Mas Ayu, Hassan; R., Daud (Penerbit Universiti Teknologi Malaysia, 2018)
One of the crucial factors which determine the success of coated implantation and stability in the long run is the strength of adhesion between the coating and substrate. After implantation, a weakly adhered coating may delaminate and this might seriously restrict the implant’s effectiveness and longevity. Based on past studies, the quality of TiN coating is directly influenced by the process parameters. The objective of this research is to evaluate the effect of N2 gas flow rate on adhesion strength of biomedical grade Ti-13Zr-13Nb alloy. In this research, N2 gas flow rate of 100, 200 and 300 sccm were varied while the other parameters (substrate temperature and bias voltage) were fixed. The scratch testing method was used to examine the adhesion strength of the TiN coating. This research used the calibrated optical images to verify the total coating failures on the scratched coated samples. The results indicated that the micro droplet form on the TiN coating decreases as the flow rate of the N2 gas increases. In contrast, the TiN coating’s adhesion strength increases with the increase of N2 gas flow rate. It can be concluded that N2 gas flow rate was significant factor in improving the coating properties of TiN on Ti-13Zr-13Nb alloy.